Small‐angle neutron scattering of long‐wavelength magnetic modulations in reduced sample dimensions. Issue 1 (15th December 2022) - Causer, Grace L.; Chacon, Alfonso; Heinemann, André; Pfleiderer, Christian
Abstract : Near‐surface SANS is discussed for its potential as a probe of long‐wavelength magnetic modulations in specimens with reduced sample dimensions. Abstract : Magnetic small‐angle neutron scattering (SANS) is ideally suited to providing direct reciprocal‐space information on long‐wavelength magnetic modulations, such as helicoids, solitons, merons or skyrmions. SANS of such structures in thin films or micro‐structured bulk materials is strongly limited by the tiny scattering volume vis a vis the prohibitively high background scattering by the substrate and support structures. Considering near‐surface scattering just above the critical angle of reflection, where unwanted signal contributions due to substrate or support structures become very small, it is established that the scattering patterns of the helical, conical, skyrmion lattice and fluctuation‐disordered phases in a polished bulk sample of MnSi are equivalent for conventional transmission and near‐surface SANS geometries. This motivates the prediction of a complete repository of scattering patterns expected for thin films in the near‐surface SANS geometry for each orientation of the magnetic order with respect to the scattering plane.